2012
DOI: 10.1016/j.jprot.2012.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoprotein abundance changes in hypertensive cardiac remodeling

Abstract: There is over-whelming evidence that protein phosphorylations regulate cardiac function and remodeling. A wide variety of protein kinases, e.g., phosphoinositide 3-kinase (PI3K), Akt, GSK-3, TGFβ, and PKA, MAPKs, PKC, Erks, and Jaks, as well as phosphatases, e.g., phosphatase I (PP1) and calcineurin, control cardiomyocyte growth and contractility. In the present work, we used global phosphoprotein profiling to identify phosphorylated proteins associated with pressure overload (PO) cardiac hypertrophy and heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 88 publications
(86 reference statements)
2
24
0
Order By: Relevance
“…Hence, it is possible that phosphorylation status of other unrecognized proteins might contribute to the disease development in PP1β deficient mice or that other phosphorylation sites exist in MLC2V or cMyBPC that have unrecognized functions that are not strictly lusitropic [49]. For example, PP1β may dephosphorylate other potential cMyBPC phosphorylation sites by kinases other than PKA, which could be pathologic [51]. Another possibility is that even a long-term enhancement in lusitropy, such as associated with greater phosphorylation of MLC2V, might ultimately lead to a chronic disease phenotype through unrecognized negative long-term consequences of this enhanced profile.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is possible that phosphorylation status of other unrecognized proteins might contribute to the disease development in PP1β deficient mice or that other phosphorylation sites exist in MLC2V or cMyBPC that have unrecognized functions that are not strictly lusitropic [49]. For example, PP1β may dephosphorylate other potential cMyBPC phosphorylation sites by kinases other than PKA, which could be pathologic [51]. Another possibility is that even a long-term enhancement in lusitropy, such as associated with greater phosphorylation of MLC2V, might ultimately lead to a chronic disease phenotype through unrecognized negative long-term consequences of this enhanced profile.…”
Section: Discussionmentioning
confidence: 99%
“…PP2A is one of the most complex members in the PPP family, regulating diverse physiological and cellular processes such as neuronal stabilization, cardiac muscle function and the cell cycle. As such, it is implicated in many human diseases such as Alzheimer’s disease, cardiac disease and cancer (Eichhorn et al ., 2009; Heijman et al ., 2013; Kotlo et al ., 2012; Martin et al ., 2013). PP2A affects such variety of processes due to the formation of diverse heterotrimeric holoenzymes.…”
Section: Protein Phosphatase 2a: a Complex And Diverse Family Of Phosmentioning
confidence: 99%
“…Toepfer, et al (Toepfer et al, 2013) also demonstrated that increased phosphorylation in rat trabeculae enhanced myocardial performance and suggested that decreased MLC-phosphorylation in cardiac disease is a key contributor to impaired cardiac contractile function. MLC phosphorylation levels were significantly reduced in pressure overloaded and failing hearts (Kotlo et al, 2012), but heart failure was prevented in MLC kinase-overexpressing mice (Warren et al, 2012). Additionally, constitutively phosphorylated cardiac MLC in mice was sufficient to prevent a hypertrophic cardiomyopathy phenotype (Karabina et al, 2015), (Yuan et al, 2015).…”
Section: Transmural Gradients As Mechanisms Of Uniform Fiber Stresmentioning
confidence: 99%